Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Science and Innovations for Food Systems Transformation 2023
DOI: 10.1007/978-3-031-15703-5_24
|View full text |Cite
|
Sign up to set email alerts
|

Food Systems Innovation Hubs in Low- and Middle-Income Countries

Abstract: In the face of global food and nutrition crises, incremental adjustment in existing technology is not enough; the future of food systems hinges on innovative solutions that can help achieve the Sustainable Development Goals (SDGs). Innovative approaches and opportunities for the transformation of food systems exist. ‘Innovations’ includes new products, business models, policy practices, technologies, behavioral insights, or ways of delivering products and services that benefit the poor in low- and middle-incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The workshop experts suggested that social marketing strategies to build knowledge, drive behavior change, and incorporate healthy practices into consumers’ lives should be part of the nutritional solutions [ 54 , 55 ]. They recognized that changing diets is not an easy task due to affordability, accessibility, among other challenges; therefore, targeted supplementation and fortification efforts may be needed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The workshop experts suggested that social marketing strategies to build knowledge, drive behavior change, and incorporate healthy practices into consumers’ lives should be part of the nutritional solutions [ 54 , 55 ]. They recognized that changing diets is not an easy task due to affordability, accessibility, among other challenges; therefore, targeted supplementation and fortification efforts may be needed.…”
Section: Resultsmentioning
confidence: 99%
“…The experts expressed that precision nutrition must be built around these key elements and goals as well as safety, ethics, and impact. Furthermore, prioritizing locally developed solutions was considered essential due to cultural differences and to support local economies [ 55 ]. Precision nutrition was viewed as useful for discovery science and to enable the evolution from one-size-fits-all approaches to accurate, targeted approaches.…”
Section: Resultsmentioning
confidence: 99%